Welcome to Westonci.ca, your go-to destination for finding answers to all your questions. Join our expert community today! Explore a wealth of knowledge from professionals across various disciplines on our comprehensive Q&A platform. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
To solve the equation [tex]\(4 \cdot 10^{-3x} = 18\)[/tex] for [tex]\(x\)[/tex], we should convert the equation into logarithmic form to make it easier to handle. Let's go through the steps:
1. Rewrite the equation using logarithms:
[tex]\[ 4 \cdot 10^{-3x} = 18 \][/tex]
2. Take the logarithm of both sides (using base 10):
[tex]\[ \log_{10}(4 \cdot 10^{-3x}) = \log_{10}(18) \][/tex]
3. Use the property of logarithms that [tex]\(\log_b(ab) = \log_b(a) + \log_b(b)\)[/tex]:
[tex]\[ \log_{10}(4) + \log_{10}(10^{-3x}) = \log_{10}(18) \][/tex]
4. Simplify the expression. Recall that [tex]\(\log_{10}(10^y) = y\)[/tex], so:
[tex]\[ \log_{10}(4) + (-3x) \log_{10}(10) = \log_{10}(18) \][/tex]
Since [tex]\(\log_{10}(10) = 1\)[/tex], the equation becomes:
[tex]\[ \log_{10}(4) - 3x = \log_{10}(18) \][/tex]
5. Isolate the term involving [tex]\(x\)[/tex]:
[tex]\[ -3x = \log_{10}(18) - \log_{10}(4) \][/tex]
6. Solve for [tex]\(x\)[/tex]:
[tex]\[ x = \frac{\log_{10}(4) - \log_{10}(18)}{-3} \][/tex]
Now let's calculate the numerical values using the given logarithmic values:
1. [tex]\(\log_{10}(4) \approx 0.6021\)[/tex]
2. [tex]\(\log_{10}(18) \approx 1.2553\)[/tex]
Substitute these values into the equation:
[tex]\[ x = \frac{0.6021 - 1.2553}{-3} \][/tex]
Calculate the numerator:
[tex]\[ 0.6021 - 1.2553 \approx -0.6532 \][/tex]
Now divide by [tex]\(-3\)[/tex]:
[tex]\[ x = \frac{-0.6532}{-3} \approx 0.2177 \][/tex]
Therefore, the exact value of [tex]\(x\)[/tex] is:
[tex]\[ x = \frac{\log_{10}(4) - \log_{10}(18)}{-3} \][/tex]
And the approximate value of [tex]\(x\)[/tex], rounded to the nearest thousandth, is:
[tex]\[ x \approx 0.218 \][/tex]
1. Rewrite the equation using logarithms:
[tex]\[ 4 \cdot 10^{-3x} = 18 \][/tex]
2. Take the logarithm of both sides (using base 10):
[tex]\[ \log_{10}(4 \cdot 10^{-3x}) = \log_{10}(18) \][/tex]
3. Use the property of logarithms that [tex]\(\log_b(ab) = \log_b(a) + \log_b(b)\)[/tex]:
[tex]\[ \log_{10}(4) + \log_{10}(10^{-3x}) = \log_{10}(18) \][/tex]
4. Simplify the expression. Recall that [tex]\(\log_{10}(10^y) = y\)[/tex], so:
[tex]\[ \log_{10}(4) + (-3x) \log_{10}(10) = \log_{10}(18) \][/tex]
Since [tex]\(\log_{10}(10) = 1\)[/tex], the equation becomes:
[tex]\[ \log_{10}(4) - 3x = \log_{10}(18) \][/tex]
5. Isolate the term involving [tex]\(x\)[/tex]:
[tex]\[ -3x = \log_{10}(18) - \log_{10}(4) \][/tex]
6. Solve for [tex]\(x\)[/tex]:
[tex]\[ x = \frac{\log_{10}(4) - \log_{10}(18)}{-3} \][/tex]
Now let's calculate the numerical values using the given logarithmic values:
1. [tex]\(\log_{10}(4) \approx 0.6021\)[/tex]
2. [tex]\(\log_{10}(18) \approx 1.2553\)[/tex]
Substitute these values into the equation:
[tex]\[ x = \frac{0.6021 - 1.2553}{-3} \][/tex]
Calculate the numerator:
[tex]\[ 0.6021 - 1.2553 \approx -0.6532 \][/tex]
Now divide by [tex]\(-3\)[/tex]:
[tex]\[ x = \frac{-0.6532}{-3} \approx 0.2177 \][/tex]
Therefore, the exact value of [tex]\(x\)[/tex] is:
[tex]\[ x = \frac{\log_{10}(4) - \log_{10}(18)}{-3} \][/tex]
And the approximate value of [tex]\(x\)[/tex], rounded to the nearest thousandth, is:
[tex]\[ x \approx 0.218 \][/tex]
We appreciate your time. Please revisit us for more reliable answers to any questions you may have. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.